Crimes against Geographical Indications: critical analysis of the legal aspects of criminal protection of Geographical Indications in Brazil - Souza, Alessandro Vitor de (2024)
Recognizing its status as a relevant legal asset, the Brazilian legal system invokes criminal law to serve as an instrument for protecting Geographical Indications. But, considering the current terms of Law n. 9.279/1996, the following question arises: is the Brazilian legislation, from a criminal perspective, effective for the protection of Geographical Indications? In this sense, the general objective of this study is to promote a critical analysis of the Brazilian legislation, from a criminal perspective. For this, a qualitative, exploratory approach was adopted, through a bibliographical review. It was found that, regarding criminal protection, the geographical indication still enjoys little prestige with the national legislator, having the lowest penalties among the other institutes of intellectual property. It was concluded that, if any effectiveness is expected regarding the criminal protection of geographical indications, in Brazil, we need an urgent reform in the Industrial Property Law.